The Impact of a New Specialized Learning Platform on Enhancing Students’ Skills in Designing and Producing Online Educational Talking Books - Mohamed Elsayed Ahmed; Shinobu Hasegawa (Education Sciences)
The use of digital audio-based learning applications in classrooms is increasing. Thus, instructional technology professionals need to become more skilled in designing and developing these apps. To succeed in the future learning process, students studying instructional technology need to have mastered these skills. This study aims to examine the impact of a specialized platform proposed to cultivate students’ skills in easily designing and producing online educational talking books (online ETBs). To improve the target abilities, we developed a new specialized platform as a web-based system for this investigation that includes several innovative tools and special learning content. The research design used was quasi-experimental. Thirty-two undergraduate students majoring in instructional technology who were in the third grade examined the proposed platform. With the pre-and post-test design, all participants were placed into one group. Three online instruments were used to gather the data: a performance observation card; a product evaluation card; and a usability questionnaire. According to the results, the suggested platform considerably increased the practical skills required to design and create an online ETB. Additionally, the proposed platform positively impacted the production of online ETB products with an acceptable proficiency level across various educational subjects. The customized platform has also proven to be a comfortable learning environment for the participating instructional technology students. This platform may be utilized as an ICT teaching tool to enhance instructional technology departments as it is appropriate for constructing online ETBs in various educational areas without coding barriers.